2013
DOI: 10.1089/scd.2012.0260
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Human Cryptorchid-Specific Induced Pluripotent Stem Cells from Urine

Abstract: Cryptorchidism is a common congenital birth defect in human beings with the possible complication of infertility. An in vitro model of cryptorchidism might be valuable due to the inaccessibility of human embryos for research purposes. In this study, we reprogrammed urine cells containing genetic variations in insulin-like factor 3, zinc finger (ZNF) 214, and ZNF215 from a cryptorchid patient by introducing human OCT4, SOX2, C-MYC, and KLF4 with lentivirus. The cells were then replated on irradiated mouse embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The latter characteristic of urine cells contributes to improved reprogramming efficiency. Our data and other investigators' studies 66 , 67 , 68 , 69 , 70 demonstrate the feasibility of rapid and efficient iPS cell generation from a sample of human urine, suggesting potential therapeutic uses of patient- derived iPS cells both for the treatment of various genetic defects via cell-based therapy and for drug screening.…”
Section: Ips Cells Reprogrammed From Uscssupporting
confidence: 68%
“…The latter characteristic of urine cells contributes to improved reprogramming efficiency. Our data and other investigators' studies 66 , 67 , 68 , 69 , 70 demonstrate the feasibility of rapid and efficient iPS cell generation from a sample of human urine, suggesting potential therapeutic uses of patient- derived iPS cells both for the treatment of various genetic defects via cell-based therapy and for drug screening.…”
Section: Ips Cells Reprogrammed From Uscssupporting
confidence: 68%
“…However, these approaches remain inefficient or laborious. We and others had previously described that epithelia-like cells could be isolated from human urine and could be further reprogrammed into iPS cells with high efficiency by using virus-based approach [13], [14], [15], [16]. Human UCs can be conveniently obtained through non-invasive method, thus representing an ideal cell source for iPS cell generation.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptorchidism involves multiple causes, such as genetic mutations and environmental factors (65,66). Researchers have established cryptorchid-specific iPSC lines with genetic variations and they have found that urine cells may represent a better source for generation of iPSCs, especially in the study of pediatric diseases (60). Most patients with complex disorders are treated with various medications over a prolonged period, which may have an impact on donor cell propagation and nuclear reprogramming.…”
Section: Modeling Rare Diseases Using Uipscsmentioning
confidence: 99%
“…Because iPSCs resemble ESCs in terms of pluripotency and the potential for self-renewal, patient-specific iPSCs could represent a promising strategy for investigating the molecular mechanisms of disease and discovery of drugs to treat them (93,94). Recent studies have reported that generating UiPSCs from patients with rare diseases would provide insight into the mechanisms of those diseases (59)(60)(61)(62)(63)(64). The availability of limitless amounts of diseased cells from patients with a rare disease could, along with gene editing, prove useful in clinical practice (Figure 1).…”
Section: Advantages Of and Barriers To The Study Of Rare Diseases Usimentioning
confidence: 99%